Protection of Consumer Personal Data in Online Loans - Bagas Sinung Pradana; Wardah Yuspin (Universitas Muhammadiyah Surakarta, 2025)
In the implementation of the Online Loan application service, it continues to receive many complaints from Pinjol customers about the problem of personal data shared by individual online loan providers. This is directly proportional to the number of pinjol consumer complaints to the Financial Services Authority, most of which contain the dissemination of personal data accompanied by threats. Therefore, it is very important for consumers to understand this regulation governing how personal data is protected when performing Online Loan services. The regulations that protect personal data in Online Loans will be discussed in this research. Applying normative legal methods, such as the implementation of laws and regulations relating to the legal protection of the parties through observation of the identification of personal data cases of online loan consumers. In its development, many online loan consumers are in arrears / have not paid off their receivables with online loans. So that opportunities arise for leaking personal data accompanied by threats in collection. Actually, this is not justified because it contradicts the regulations for organizing online loans stipulated in the Financial Services Authority Regulation Number 10/POJK.05/2022 Article 47 which states that to collect and use personal data, the organizer must obtain the consent of the data owner. So as to further strengthen the legal power for online loan consumers in protecting their personal data, there is a Republican Law Number 27 of 2022 concerning Personal Data Protection consisting of 78 articles spread over 18 chapters that regulate the transfer of personal data. These documents address a variety of issues, such as institutions, international collaboration, community involvement, administrative sanctions, dispute resolution, and civil legal proceedings. It also includes provisions regarding uses of personal data prohibited by law, penal provisions, transitional measures, and concluding clauses.